Application of Taguchi approach to optimize of FSSW parameters on joint properties of dissimilar AA2024-T3 and AA5754-H22 aluminum alloys - BİLİCİ, MUSTAFA KEMAL; BOZKURT, YAHYA (ELSEVIER SCI LTD, 2013)
In this study, the effect of plate positioning on mechanical properties of dissimilar lap joints was investigated by friction stir spot welding (FSSW) process. The determination of the welding parameters plays an important role for the weld strength. For the effective use of the dissimilar aluminum joints, the FSSW must have an adequate strength. The quality of the joint was evaluated by examining the characteristics of the joining efficiency as a result of the lap-shear tensile test. Four process parameters were selected: the tool rotation speed, dwell time, tool plunge depth, and tilt angle. The process parameters were optimized by Taguchi technique based on Taguchi's L9 orthogonal array. The optimum welding process parameters were predicted, and their percentage of contribution was estimated by applying the signal-to-noise ratio and analysis of variance. The experimental results showed that the positioning of the plates played an important role on the strength of the joints. Finally, the results were confirmed by further experiments. Crown Copyright (c) 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: STIR SPOT WELDS; FRICTION; RESISTANCE; STRENGTH; TOOL